2009
DOI: 10.1088/0953-8984/21/17/174210
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport in n- and p-type modulation doped GaxIn1−xNyAs1−y/GaAs quantum wells

Abstract: We present a comprehensive study of longitudinal transport of two-dimensional (2D) carriers in n- and p-type modulation doped Ga(x)In(1-x)N(y)As(1-y) /GaAs quantum well structures. The Hall mobility and carrier density of electrons in the n-modulation doped quantum wells (QWs) decreases with increasing nitrogen composition. However, the mobility of the 2D holes in p-modulation doped wells is not influenced by nitrogen and it is significantly higher than that of 2D electrons in n-modulation doped material. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…However, for the sample with the lowest Ga concentration, Ga 0.06 In 0.94  N, it decreases from 1,035 to 890 cm 2 /Vs with increasing temperature from 100 to 300 K but does not show any significant change in the other two samples, which is a characteristic feature of metallic-like semiconductors [7,26,27]. The insensitivity of carrier mobility to temperature is commonly observed in polar materials with elevated carrier densities where the polar interactions are screened [19,25,29-33]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the sample with the lowest Ga concentration, Ga 0.06 In 0.94  N, it decreases from 1,035 to 890 cm 2 /Vs with increasing temperature from 100 to 300 K but does not show any significant change in the other two samples, which is a characteristic feature of metallic-like semiconductors [7,26,27]. The insensitivity of carrier mobility to temperature is commonly observed in polar materials with elevated carrier densities where the polar interactions are screened [19,25,29-33]. …”
Section: Resultsmentioning
confidence: 99%
“…At high temperatures, however, interface roughness and alloy potential restrict the mobility, but effect of the dislocation scattering becomes less dominant as a result of shortening Debye screening length due to higher carrier density. Furthermore, in the high-carrier-concentration regime, electron–phonon scattering is heavily screened, as described above and in references [19,25,29-33]. …”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, in the presence of the nitrogen, it has been theoretically demonstrated that hole effective mass and hole mobility remain unaffected [14-16]. So far, much effort has been focused on nitrogen dependence of electron effective mass and electron mobility, ignoring the composition dependence of hole effective mass and hole mobility.…”
Section: Reviewmentioning
confidence: 99%
“…Therefore, in material with relatively high nitrogen incorporation, the hole mobility can be higher than the electron mobility at low temperature because of both smaller effective mass and the lack of scattering by nitrogen complexes as observed in our previous studies. 16,17 The high hole mobility provides the motivation for the current work, i.e., to establish a full understanding of hole transport, particularly at high electric field for their potential application in ultrafast novel devices.…”
Section: Introductionmentioning
confidence: 99%